Clinical Presentation of Dengue Fever among Bangladeshi Children: A Study of 100 Cases - Taher, Tania; Ashraf, Sumala; Haroon, Kaisar; Fatmi, L E (Bangladesh Journal of Infectious Diseases, 2023)
Background: Dengue is a common tropical disease in Bangladesh. It is prevalent in our country during and just after the rainy season. The symptoms and signs are similar to many other diseases. Objective: The objective of the study is to observe the pattern of dengue fever in this institution for better care of the patients and also comparing with follow-up studies. Methodology: This cross-sectional study was conducted in the Department of Pediatrics at Holy Family Red Crescent Medical College Hospital, Dhaka, Bangladesh from May 2019 to August 2019. A total number of 100 patients were enrolled for this study. They were selected form the inpatient admission. Results: Most commonly children from the 5 to 10 years’ age group were affected with slight preponderance of girls. 90% patients presented with fever with chills and rigor. About 38.18 % children had uncomplicated dengue fever. Most common bleeding manifestation was melena (12.0%). About 21 patients had associated rickettsia infections. About 11 patients developed shock after admission only 22 patients had respiratory distress and 15 patients had pleural effusion. Six patients had neurological symptoms. Conclusions: Classical DF is most common form of the disease. This is followed by other two manifestations. Bangladesh Journal of Infectious Diseases, June 2022;9(1):25-30